Analisa dan Perancangan Sistem Informasi Pembayaran Air HIPPAM Desa Leran Berbasis Web - Putri Maulidiyah Rif’atul Rizkiyah; Ctevani Auliyan Putra; Saffana Assani'; Hermanto Hermanto (KONSTELASI: Konvergensi Teknologi dan Sistem Informasi, 2021)
The HIPPAM of Leran Desa is a village-owned company that works to provide clean water for the people of Leran Village. The process of recording meters and water payments for HIPPAM still uses a manual system (notebook and simple application on Microsoft Excel), so that errors often occur such as inaccurate data and not responding to excel documents. Not only that, but the payment process takes a lot of time so it is less efficient. For this reason, a web-based payment system is needed that can solve these problems and simplify the process of payment for water from the Leran village HIPPAM, so that the resulting data are minimal errors and reduce long queues in the payment process, this system can be used by customers to view bill payments, and filing a complaint if there is a problem in the HIPPAM water either about the water meter or service. This research consists of analysis and design, while the methodology used to develop the system is SDLC (system development life cycle). The results of this research are in the form of a system design and analysis document that will be used to develop this HIPPAM payment system. The analysis document contains functional requirements analysis and non-functional requirements analysis, for the design document there is DFD design or data flow diagrams and user interface design.